(3OjhGf GHf OQGL GdbSWdis - (3CHhYeQ CMeO Hf eMeO Hf GdYGU Hf OQGL GdbSWdj GdCfOdSj,J (B421 (3g` s
(3ChdgG (B:s
(3jHOC CKfGA bUjOI dGejI eVeheI Chd eG ajg efgG ceG QaY GdBd GdQhGQL HGdVMi ZOGI GSJbHdJ HGdNdjW Mehd s
(3BNQgG (B:s
(3jfJgi HbUjOI cJHgG Edi Phi GdcaGjJjf JGL GdOhdg GHf CHj GdMSjf HeUQ hBNQ eG ajgG (B: (3jdhM HgG fLe ef GdCab WGdY hjQLYgG Edi efc eG ZGQZGFQ s
(3ZjQ eQJH Ydi GdbhGais
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B114s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdCOHs